Novel porous scaffolds of pH responsive chitosan/carrageenan‐based polyelectrolyte complexes for tissue engineering. Issue 12 (25th February 2014) - Araujo, J. V.; Davidenko, N.; Danner, M.; Cameron, R. E.; Best, S. M.
Abstract Polyelectrolyte complexes (PECs) represent promising materials for drug delivery and tissue engineering applications. These substances are obtained in aqueous medium without the need for crosslinking agents. PECs can be produced through the combination of oppositely charged medical grade polymers, which include the stimuli responsive ones. In this work, three‐dimensional porous scaffolds were produced through the lyophilization of pH sensitive PECs made of chitosan (CS) and carrageenan (CRG). CS:CRG molar ratios of 1:1 (CSCRG1), 2:1 (CSCRG2), and 3:1 (CSCRG3) were used. The chemical compositions of the PECs, as well as their influence in the final structure of the scaffolds were meticulously studied. In addition, the pH responsiveness of the PECs in a range including the physiological pH values of 7.4 (simulating normal physiological conditions) and 4.5 (simulating inflammatory response) was assessed. Results showed that the PECs produced were stable at pH values of 7.4 and under but dissolved as the pH increased to nonphysiological values of 9 and 11. However, after dissolution, the PEC could be reprecipitated by decreasing the pH to values close to 4.5. The scaffolds obtained presented large and interconnected pores, being equally sensitive to changes in the pH. CSCRG1 scaffolds appeared to have higher hydrophilicity and therefore higher water absorption capacity. The increase in the CS:CRG molar ratios improved the scaffold mechanical properties, with CSCRG3 presenting the higher compressive modulus under wet conditions. Overall, the PEC scaffolds appear promising for tissue engineering related applications that require the use of pH responsive materials stable at physiological conditions. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4415–4426, 2014.